2010
DOI: 10.1007/s10661-010-1722-y
|View full text |Cite
|
Sign up to set email alerts
|

The potential of the Phytotoxkit microbiotest for hazard evaluation of sediments in eutrophic freshwater ecosystems

Abstract: The applicability of the Phytotoxkit microbiotest for toxicity assessment of sediments in eutrophic freshwater ecosystems was evaluated. Sediments were collected from Turawa dam reservoir (southwestern Poland) which, for years, has been subjected to a marked nutrient enrichment and heavy metal contamination. The test plant species were exposed to whole sediments, solid phases of sediments, and pore waters. Phytotoxicity was estimated on the basis of seed germination and root elongation measurements, combined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 32 publications
1
30
1
3
Order By: Relevance
“…Seeds used in the test have enough energy required for germination and growth during test exposure and would not be influenced by a lack of nutrients in test sediment, thus only indicating the toxicity of the sediment itself (Persoone, 2013). The results from a study by Czerniawska-Kusza et al (2006) showed that growth inhibition and stimulation effects can vary between plant species due to the sediment contaminant composition. The findings from this study show that the Phytotoxkit and the Ostracodtoxkit F are sensitive enough to indicate sediment toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds used in the test have enough energy required for germination and growth during test exposure and would not be influenced by a lack of nutrients in test sediment, thus only indicating the toxicity of the sediment itself (Persoone, 2013). The results from a study by Czerniawska-Kusza et al (2006) showed that growth inhibition and stimulation effects can vary between plant species due to the sediment contaminant composition. The findings from this study show that the Phytotoxkit and the Ostracodtoxkit F are sensitive enough to indicate sediment toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The Phytotoxkit test is conducted using three plant species (Lepidium sativum, Sinapis alba and Sorghum saccharatum). This test kit has been used by Czerniawska-Kusza et al (2006) to evaluate the toxicity of canal sediment; Czerniawska- Kusza and Kusza (2011) to test the toxicity of reservoir sediment and Van der Vliet et al (2012) to evaluate various pollutants. Currently in South Africa there are no standardised methods to evaluate the status of potentially contaminated sediments.…”
Section: Introductionmentioning
confidence: 99%
“…The sediments are naturally formed by the precipitation of particles formed in the overlying water column. These suspended particles adsorbs nutrients and contaminants and in sedimentation process transfer them from the water column to the sediment (Czerniawska-Kusza and Kusza, 2011). Soluble forms of Cd can migrate in the water column, while insoluble forms of Cd can sediment and adsorb to the substrate (ATSDR, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Quando aderidos aos sólidos em suspensão, os contaminantes presentes na coluna d'água tendem a ser transportados por longas distâncias ou sedimentar durante o percurso, contaminando outros trechos do corpo hídrico (Czerniawska-Kusza & Kusza, 2011). Por este motivo é crescente a preocupação com o potencial poluidor dos sedimentos de corpos d'água que recebem efluentes domésticos ou industriais.…”
Section: Introductionunclassified
“…Testes em que se utilizam plantas superiores são considerados eficientes para a avaliação e monitoramento da toxicidade de poluentes e têm sido utilizados em estudos sobre a fitotoxicidade de águas e sedimentos contaminados (Fernandes et al, 2007;Czerniawska-Kusza & Kusza, 2011). Sua principal vantagem é a ampla variedade de parâmetros de toxicidade, como a taxa de germinação, ganho de biomassa, alongamento de raízes e aspectos bioquímicos, além de apresentar baixo custo e possibilidade de serem realizados continuamente (Žaltauskaitė & Čypaitė, 2008).…”
Section: Introductionunclassified